Functional imaging of RAS pathway targeting in malignant peripheral nerve sheath tumor cells and xenografts. Issue 12 (25th September 2020) - Butler, Erin; Schwettmann, Blake; Geboers, Sophie; Hao, Guiyang; Kim, Jiwoong; Nham, Kien; Sun, Xiankai; Laetsch, Theodore W.; Xu, Lin; Williams, Noelle S.; Skapek, Stephen X.
Abstract: Background: Malignant peripheral nerve sheath tumor (MPNST) is an aggressive form of soft‐tissue sarcoma (STS) in children. Despite intensive therapy, relatively few children with metastatic and unresectable disease survive beyond three years. RAS pathway activation is common in MPNST, suggesting MEK pathway inhibition as a targeted therapy, but the impact on clinical outcome has been small to date. Procedure: We conducted preclinical pharmacokinetic (PK) and pharmacodynamic studies of two MEK inhibitors, trametinib and selumetinib, in two MPNST models and analyzed tumors for intratumor drug levels. We then investigated 3′‐deoxy‐3′‐[ 18 F]fluorothymidine ( 18 F‐FLT) PET imaging followed by 18 F‐FDG PET/CT imaging of MPNST xenografts coupled to short‐term or longer‐term treatment with selumetinib focusing on PET‐based imaging as a biomarker of MEK inhibition. Results: Trametinib decreased pERK expression in MPNST xenografts but did not prolong survival or decrease Ki67 expression. In contrast, selumetinib prolonged survival of animals bearing MPNST xenografts, and this correlated with decreased pERK and Ki67 staining. PK studies revealed a significantly higher fraction of unbound selumetinib within a responsive MPNST xenograft model. Thymidine uptake, assessed by 18 F‐FLT PET/CT, positively correlated with Ki67 expression in different xenograft models and in response to selumetinib. Conclusion: The ability of MEK inhibitors to control MPNST growth cannot simply be predicted by serum drug levels or drug‐induced changes in pERK expression. Tumor cell proliferation assessed by 18 F‐FLT PET imaging might be useful as an early response marker to targeted therapies, including MEK inhibition, where a primary effect is cell‐cycle arrest.